ACTIVITY MORNING (SELASA LITERASI) SEBAGAI STRATEGI MEMBANGUN LINGKUNGAN SEKOLAH BERLITERASI - Tina Rumeuw; Winarno; Tiara Kusuma Dewi; Tika Febryana Setianingrum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The Activity Morning Program in the form of Selasa Literasi is a school literacy innovation designed to foster a literacy-oriented school environment in vocational high schools. This study aims to evaluate the implementation of the Activity Morning Program, analyze its impact on students’ literacy habits and attitudes, and identify supporting and inhibiting factors in its implementation at SMK Negeri 3 Salatiga. This research employed a descriptive qualitative method involving students, literacy teachers, librarians, and school management as research participants. Data were collected through observation, in-depth interviews, and documentation, with data validity ensured through method triangulation, source triangulation, and member checking. The findings indicate that the Selasa Literasi program has been implemented consistently and in accordance with established guidelines. The program is conducted every Tuesday for 40 minutes before formal lessons begin and includes various literacy activities such as reading, writing summaries, composing short opinions, creating concept maps, and practicing numeracy skills. The program has a positive impact on improving students’ reading habits, short writing skills, learning readiness, and the development of a more literate school environment both physically and socially. Teachers play a crucial role in maintaining discipline, providing guidance, and enhancing the quality of literacy activities. However, challenges remain, particularly related to limited reading materials and uneven student motivation across classes. Overall, the Activity Morning Program through Selasa Literasi is effective as a literacy habituation strategy and has strong potential to be further developed and replicated in other vocational high schools. ABSTRAKProgram Activity Morning dalam bentuk Selasa Literasi merupakan salah satu inovasi literasi sekolah yang dikembangkan untuk membangun budaya literasi di Sekolah Menengah Kejuruan (SMK). Penelitian ini bertujuan untuk mengevaluasi keterlaksanaan Program Activity Morning, menganalisis dampaknya terhadap kebiasaan dan sikap literasi siswa, serta mengidentifikasi faktor pendukung dan penghambat pelaksanaannya di SMK Negeri 3 Salatiga. Penelitian ini menggunakan metode deskriptif kualitatif dengan subjek penelitian meliputi siswa, guru pendamping literasi, pustakawan, dan pihak manajemen sekolah. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi, dengan validitas data dijaga melalui triangulasi metode, triangulasi sumber, dan member checking. Hasil penelitian menunjukkan bahwa pelaksanaan Selasa Literasi berjalan secara konsisten dan sesuai dengan pedoman yang telah ditetapkan sekolah. Program ini dilaksanakan setiap hari Selasa selama 40 menit sebelum pembelajaran dimulai dan melibatkan aktivitas membaca, menulis ringkasan, menulis opini, pembuatan peta konsep, serta latihan numerasi. Selasa Literasi berdampak positif terhadap peningkatan kebiasaan membaca, kemampuan menulis singkat, kesiapan belajar siswa, serta terbentuknya lingkungan sekolah yang lebih literat baik secara fisik maupun sosial. Peran guru pendamping terbukti sangat penting dalam menjaga disiplin, memberikan bimbingan, dan meningkatkan kualitas kegiatan literasi. Meskipun demikian, masih ditemukan kendala berupa keterbatasan variasi bahan bacaan dan motivasi siswa yang belum merata. Secara keseluruhan, Program Activity Morning melalui Selasa Literasi efektif sebagai strategi pembiasaan literasi dan berpotensi dikembangkan serta direplikasi di SMK lain.